PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PAK PADA SISWA KELAS IIIB SDK YOS SUDARSO MAUMERE - Carina Du’a Mine (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the improvement of student learning outcomes in Catholic Religious Education subjects through the application of Jigsaw-type cooperative learning in grade IIIB students of SDK Yos Sudarso Maumere. The type of research used is classroom action research with two cycles consisting of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were grade IIIB students consisting of 22 students. The results showed that the application of the Jigsaw-type cooperative learning model in learning was classified as very good and was able to trigger maximum student involvement in the learning process so as to improve learning outcomes. Student learning outcomes have changed for the better after applying the Jigsaw type cooperative learning model in learning. Student learning outcomes improve because students are very enthusiastic and actively participate with the application of the Jigsaw-type cooperative learning model.